2011
DOI: 10.1182/blood-2010-12-325951
|View full text |Cite
|
Sign up to set email alerts
|

β2-Glycoprotein I: a novel component of innate immunity

Abstract: Sepsis is a systemic host response to invasive infection by bacteria. Despite treatment with antibiotics, current mortality rates are in the range of 20%-25%, which makes sepsis the most important cause of death in intensive care. Gram-negative bacteria are a prominent cause of sepsis. Lipopolysaccharide (LPS), one of the major constituents of the outer membrane of Gram-negative bacteria, plays a major role in activating the host's immune response by binding to mono-cytes and other cells. Several proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 38 publications
6
125
0
Order By: Relevance
“…34 Thus, one role of PF4 might also be to protect from endotoxic shock, as has been shown for ␤ 2 -glycoprotein I. 35 Lipid A also binds antimicrobial peptides, such as the bactericidal/permeability-increasing protein (BPI) 36,37 and the cyclic lipopeptide polymyxin B, which interacts with the phosphate groups of lipid A. [38][39][40][41][42] In line with our other findings, BPI and polymyxin B inhibited PF4 binding to isolated lipid A ( Figure 3B), further confirming that PF4 interacts with lipid A.…”
Section: Discussionmentioning
confidence: 99%
“…34 Thus, one role of PF4 might also be to protect from endotoxic shock, as has been shown for ␤ 2 -glycoprotein I. 35 Lipid A also binds antimicrobial peptides, such as the bactericidal/permeability-increasing protein (BPI) 36,37 and the cyclic lipopeptide polymyxin B, which interacts with the phosphate groups of lipid A. [38][39][40][41][42] In line with our other findings, BPI and polymyxin B inhibited PF4 binding to isolated lipid A ( Figure 3B), further confirming that PF4 interacts with lipid A.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, human homozygotes for β2GP1 deficiency do not present any clinical complications [27]. The function of β2GP1 proteins in APS was recently re-evaluated by Agar et al [28]. β2GP1 appears to modulate the innate immune system through its ability to downregulate LPS-induced TF and IL-6 expression by monocytes.…”
Section: Cell Activation By Aplamentioning
confidence: 99%
“…It took quite a while to unravel the physiologic role of β 2 GPI: only recently, two independent groups demonstrated that the C-terminal of the protein interacts specifically with lipopolysaccharide (LPS). Such observation suggests β 2 GPI may act as a carrier or as a scavenger for LPS [8,9]. The interaction between β 2 GPI and LPS is further supported by the inverse correlation between plasma levels of β 2 GPI and inflammatory markers such as tumour necrosis factor (TNF) α, interleukin (IL)-6 and IL-8.…”
Section: Anti-phospholipid Antibodies In Systemic Lupus Erythematosusmentioning
confidence: 87%
“…The interaction between β 2 GPI and LPS is further supported by the inverse correlation between plasma levels of β 2 GPI and inflammatory markers such as tumour necrosis factor (TNF) α, interleukin (IL)-6 and IL-8. Moreover, in vivo LPS injection induced a 25% reduction of baseline β 2 GPI serum levels [8].…”
Section: Anti-phospholipid Antibodies In Systemic Lupus Erythematosusmentioning
confidence: 95%